Toward a Tripartite Model of EFL Students’ Learning Strategies, Epistemic Beliefs, and Their Online Learning Engagement - Emaliana, Ive; Lintangsari, Alies Poetri; Mulia, Dimas Rizki (FKIP Universitas Lampung, 2022)
Toward a Tripartite Model of EFL Students’ Learning Strategies, Epistemic Beliefs, and Their Online Learning Engagement. Objectives: The main objective of this study is to understand the link between these factors. This research explored the link among EFL students’ learning, beliefs about learning, learning strategies, and learning engagement since they are key factors in influencing them to learn English. Methods: This research applied quantitative research, notably correlational design among EFL epistemic belief, learning strategies which later is consisted of reading, speaking, and writing, and online learning engagement. Findings: The findings of structural equation modeling showed that EFL epistemic beliefs are associated with learning strategies and online learning engagement in a significant and positive way. Conclusion: Theoretical and methodological implications for studies of epistemic beliefs, learning strategies, and online learning engagement are explored. Keywords: tripartite model, EFL students, epistemic belief, learning strategies, online learning engagement.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202215